2009
DOI: 10.1007/s10899-009-9116-1
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of Abstinence and Controlled Gambling as Self-Selected Goals of Treatment for Female Pathological Gambling

Abstract: The current study aimed to provide a preliminary evaluation of the differential efficacy of a cognitive-behavioural treatment program for female pathological gamblers delivered with the goals of abstinence or controlled gambling. The findings were based on the comparison of pathological gamblers selecting abstinence and pathological gamblers selecting controlled gambling on measures of gambling behaviour and psychological functioning. The findings revealed that pathological gamblers selecting controlled gambli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 40 publications
0
40
0
2
Order By: Relevance
“…Moreover, research has demonstrated the viability of moderation treatment goals-most often for alcohol use and gambling disorders than for illicit substance use disorders-and has suggested that offering these goals might provide a more realistic, attractive option for clients, and might lead to lower attrition rates by increasing self-efficacy and motivation early in treatment (Blaszczynski, McConaghy, & Frankova, 1991;Booth, Dale, & Ansari, 1984;Ladouceur, Lachance, & Fournier, 2009;Marlatt & Donovan, 2005;. Beyond a client merely having a moderation goal in treatment, moderation-focused treatments for alcohol use and gambling disorders have been specifically developed and tested that help clients work explicitly towards moderation goals and that incorporate moderation-focused techniques (Dowling, Smith, & Thomas, 2009;Ladouceur et al, 2009;Marlatt & Witkiewitz, 2002;Saladin & Santa Ana, 2004). For example, in the alcohol literature, several treatment approaches to controlled drinking have been found to be efficacious, including behavioural self-control training (Hester, 1995), moderation-oriented cue exposure (Drobes, Saladin, & Tiffany, 2001), guided self-change , and other interventions based on harm reduction principles (Marlatt & Witkiewitz, 2002;Saladin & Santa Ana, 2004).…”
Section: Overview In the Addictive Disorders Literaturementioning
confidence: 99%
“…Moreover, research has demonstrated the viability of moderation treatment goals-most often for alcohol use and gambling disorders than for illicit substance use disorders-and has suggested that offering these goals might provide a more realistic, attractive option for clients, and might lead to lower attrition rates by increasing self-efficacy and motivation early in treatment (Blaszczynski, McConaghy, & Frankova, 1991;Booth, Dale, & Ansari, 1984;Ladouceur, Lachance, & Fournier, 2009;Marlatt & Donovan, 2005;. Beyond a client merely having a moderation goal in treatment, moderation-focused treatments for alcohol use and gambling disorders have been specifically developed and tested that help clients work explicitly towards moderation goals and that incorporate moderation-focused techniques (Dowling, Smith, & Thomas, 2009;Ladouceur et al, 2009;Marlatt & Witkiewitz, 2002;Saladin & Santa Ana, 2004). For example, in the alcohol literature, several treatment approaches to controlled drinking have been found to be efficacious, including behavioural self-control training (Hester, 1995), moderation-oriented cue exposure (Drobes, Saladin, & Tiffany, 2001), guided self-change , and other interventions based on harm reduction principles (Marlatt & Witkiewitz, 2002;Saladin & Santa Ana, 2004).…”
Section: Overview In the Addictive Disorders Literaturementioning
confidence: 99%
“…Unsurprisingly, others have found that such differences dissipate if clients are allowed to choose between therapy goals of abstinence or controlled gambling or to set their own goals (Dowling, Smith, & Thomas, 2009). SGTS clients are encouraged to set their own therapy goals and these were examined to see if there were any differences in the types of goals set between the two groups.…”
Section: Treatment Goalsmentioning
confidence: 99%
“…For these participants controlled gambling behavior was the stated or achieved treatment goal. Controlled gambling behavior is a broadly accepted therapeutic goal (Blaszczynski, McConaghy, & Frankova, 1991;Dowling & Smith, 2007;Dowling, Smith, & Thomas, 2009;Ladouceur, 2005).…”
Section: Participantsmentioning
confidence: 99%